Perkembangan Paradigma Filolog Britania Raya terhadap Mushaf Kuno Nusantara - Zainal Abidin; Norma Azmi Farida (Tashwirul Afkar, 2022)
The British Library has a collection of 8 Southeast Asian Quranic manuscripts which have now been digitized. The Quranic manuscripts were collected from the 19th century until 2012. Initially, colonial philologists paid little attention to Quranic manuscripts and prayer’s books in Arabic. In fact, until the end of the 20th century there were only two copies of the ancient Qur’anic manuscripts there. This article wants to describe the development of the paradigm of British philologists and librarians at the British Library towards the ancient Qur’anic manuscripts of Nusantara. This study focuses on three Quranic manuscripts from the Javanese collection of John Crawfurd and Russel Jones with the code Add 12312, Add12343, and Or16877. These three manuscripts will be analyzed for their characteristics. The data used were sourced from literature review and interviews which were processed descriptively and analytically. The results of this study indicate a process that perceives the philologists and librarians in the British Library towards Quranic manuscripts of Nusantara, from the assumption that the manuscripts are not valuable to be valuable. This article also describes historical data related to the role of John Crawfurd and Russell Jones in tracing the Javanese Quranic manuscripts.